2016
DOI: 10.1111/pre.12156
|View full text |Cite
|
Sign up to set email alerts
|

Diatom (Bacillariophyceae) assemblages in salt marshes of south‐central Chile: Relations with tidal inundation time and salinity

Abstract: SUMMARYTo reconstruct sea-level history from changes in tidal environments using diatom assemblages, we need to better understand the relations among brackish diatom assemblages and changing environments along elevational gradients from diverse coastal sites. Our statistical analysis reveals relations between environmental variables and brackish benthic diatom assemblages in the little studied region of south-central Chile. Along four transects across salt marshes at two sites, we identified 224 diatom taxa in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…Our data agree to some extent with the data obtained by Touliabah [4,16] and Sawai [80].Touliabah [16] recorded the Bacillariophyceae as the second dominant group after Dinophyceae. They reported that, the percentage abundance of this group was 27.9% of the total phytoplankton standing crop in Jeddah.…”
Section: Resultssupporting
confidence: 82%
“…Our data agree to some extent with the data obtained by Touliabah [4,16] and Sawai [80].Touliabah [16] recorded the Bacillariophyceae as the second dominant group after Dinophyceae. They reported that, the percentage abundance of this group was 27.9% of the total phytoplankton standing crop in Jeddah.…”
Section: Resultssupporting
confidence: 82%
“…Diatoms (unicellular algae) are widely used for this purpose due to their vertical zonation in intertidal environments, as well as their high preservation potential in coastal sediments (for full reviews see Pilarczyk et al, 2014 andDura et al, 2016). In Chile, modern diatom data are available only from a limited number of sites (Nelson et al, 2009;Garrett et al, 2013;Sawai et al, 2017). Consequently, as we attempt to reconstruct palaeoseismic deformation at new sites or further back in time, our models may be limited by not having a modern-day equivalent of the past environment we are trying to reconstruct.…”
Section: Introductionmentioning
confidence: 99%
“…), and the loss of MPB Chl a may be much higher at JYI than at DYI owing to the turbulent environment from Jiulong River runoff and the tidal current (Sawai et al . ). Thus, the balance between growth and loss of MPB resulted in a lower MPB Chl a at JYI, and the analysis showed differential responses of MPB diatoms to the ENV1 between the two sites (Fig.…”
Section: Discussionmentioning
confidence: 97%